2022
DOI: 10.1002/rse2.289
|View full text |Cite
|
Sign up to set email alerts
|

Tracking canopy gaps in mangroves remotely using deep learning

Abstract: Mangroves are among the most ecologically valuable ecosystems of the globe. Reliable remote sensing solutions are required to assist their management and conservation at broad scale. Canopy gaps are part of forests' turnover and rejuvenation, but yet no method has been proposed to map their occurrence and recovery in mangroves. Here, were propose an approach based on a deep learning framework called Mask R-CNN to achieve automatic detection and delineation of gaps using very-high-resolution satellite imagery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 70 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Originally, the NNDiffuse algorithm was designed to be a radiometrically accurate pansharpening algorithm and has been used in both commercial geospatial packages (e.g., ENVI) as well as in research applications. [10][11][12][13][14] In previous work, 5,6 we demonstrated that NNDiffuse can be extended to the problem of LRHSI+HRMSI fusion, that is, spatially enhancing a low-res HSI using a high-res MSI. In Ref., 6 we explained in detail how the LRHSI+HRMSI fusion is broken down into b separate pansharpening tasks, where b is the number of highresolution bands in the HRMSI.…”
Section: Leveraging Spatial Featuresmentioning
confidence: 98%
“…Originally, the NNDiffuse algorithm was designed to be a radiometrically accurate pansharpening algorithm and has been used in both commercial geospatial packages (e.g., ENVI) as well as in research applications. [10][11][12][13][14] In previous work, 5,6 we demonstrated that NNDiffuse can be extended to the problem of LRHSI+HRMSI fusion, that is, spatially enhancing a low-res HSI using a high-res MSI. In Ref., 6 we explained in detail how the LRHSI+HRMSI fusion is broken down into b separate pansharpening tasks, where b is the number of highresolution bands in the HRMSI.…”
Section: Leveraging Spatial Featuresmentioning
confidence: 98%
“…The semantic segmentation prediction also enables us to study the gaps between trees or those separating forest stands. This helps to understand the growth patterns of the whole mangrove forest and the species distributions, depending on environmental variables, such as distance to shore, tidal locations, forest cover loss and water channel formation [29]. It can also aid in detecting deforestation incidents or other disturbances in the environment.…”
Section: Seeing the Forest For The Trees: An Inven(s)torymentioning
confidence: 99%
“…Paired with machine learning automation, studies of long time-series of images can be carried out. Recent improvements in satellite image resolutions (i.e., 0.031 m for the World-View 3 satellite) have allowed for more resolved classification of trees using semantic segmentation neural networks [23,24], detection of individual trees using instance segmentation networks [25][26][27][28] and detection of mangrove forest clearings [29] on highresolution RGB images. Nonetheless, the calculation of certain variables, such as the height of trees extracted from canopy height models (CHMs) is error-prone at the current resolution of satellite imagery and should be paired with low-flying platforms, such as planes or UASs [28] for better validation and performance.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 26, NNDiffuse was used to spatially enhance WV-3 and WorldView-4 images for tracking canopy gaps in mangroves using a Mask R-CNN algorithm. In Ref.…”
Section: Introductionmentioning
confidence: 99%